2013
DOI: 10.1016/j.metabol.2013.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Sagittal abdominal diameter as a marker for epicardial adipose tissue in premenopausal women

Abstract: SAD, a simple anthropometric measure, accurately estimated EAT and thus represents a clinically useful non-invasive marker that can identify patients with EAT accumulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Weight was measured on an electronic digital scale positioned on a flat surface, with a maximum capacity of 200 kg and a sensitivity of 100 g. The SAD was measured to the nearest 0.1 cm after a normal exhalation while the subjects were in a supine position with their knees slightly bent on a firm examination table. The measurement was taken at the umbilicus level using the Holtain-Kahn Abdominal Caliper (Holtain Ltd, Crymych, United Kingdom), a portable sliding-beam caliper [ 15 ], [ 19 ]. Waist circumference was measured in a standing position by a flexible and inelastic measuring tape (TBW Ltd, Brazil) at the umbilicus level after a normal exhalation without clothing in the measurement area and taking the necessary care not to compress the tissues.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Weight was measured on an electronic digital scale positioned on a flat surface, with a maximum capacity of 200 kg and a sensitivity of 100 g. The SAD was measured to the nearest 0.1 cm after a normal exhalation while the subjects were in a supine position with their knees slightly bent on a firm examination table. The measurement was taken at the umbilicus level using the Holtain-Kahn Abdominal Caliper (Holtain Ltd, Crymych, United Kingdom), a portable sliding-beam caliper [ 15 ], [ 19 ]. Waist circumference was measured in a standing position by a flexible and inelastic measuring tape (TBW Ltd, Brazil) at the umbilicus level after a normal exhalation without clothing in the measurement area and taking the necessary care not to compress the tissues.…”
Section: Methodsmentioning
confidence: 99%
“…In 1996, SAD, anthropometrically measured, was proposed as a surrogate marker of visceral fat mass [ 8 ], [ 9 ], which has recently become more established [ 10 – 12 ]. Some studies also demonstrated a better performance of SAD compared to waist circumference in the assessment of visceral fat [ 13 ], [ 14 ] and epicardial fat [ 15 ]. Moreover, SAD was considered an independent predictor of sudden death [ 16 ] and arterial stiffness [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study we have also, for the first time, investigated SAD as a predictor of AF and found that SAD is incrementally associated with an increased risk of AF. WC and SAD are both measures of abdominal obesity, but SAD correlates better with MetS [ 39 ], CVD risk factors [ 40 ], incident CVDs [ 10 ] and the amount of visceral- [ 41 ] and epicardial [ 42 ] adipose tissue. Since visceral- and epicardial adipose tissue have a high secretion of inflammatory mediators, adipokines [ 40 ], and because inflammation is associated with the risk of AF [ 43 ], we hypothesized that SAD would have a higher predictive value of AF risk than WC.…”
Section: Discussionmentioning
confidence: 99%
“…23 Currently, sagittal abdominal diameter, which has emerged as a surrogate marker of visceral obesity, accurately estimated cardiac fat deposits when compared with BMI and, thus, represents a clinically helpful non-invasive parameter that can identify patients with cardiac fat deposits. 37 Pericardial fat has been reported to contain higher levels of inflammatory markers than does subcutaneous fat, and several studies have suggested that pericardial fat has a local pathogenic effect on surrounding coronary arteries, whereas subcutaneous fat exerts a systemic effect in enhancing the insulin resistance. 21 No significant correlation existed between the number of coronary vessel involvement and PFV, and patients with normal coronary arteries were noted to have lower PFV values than patients with stenotic lesions in our study.…”
Section: Discussionmentioning
confidence: 99%